Boron supply alleviates Al-induced inhibition of root elongation and physiological characteristics in rapeseed (Brassica napus L.). Issue 1 (1st January 2018) - Riaz, Muhammad; Wu, Xiuwen; Yan, Lei; Hussain, Saddam; Aziz, Omar; Shah, Asad; Jiang, Cuncang
ABSTRACT: Aluminum (Al) toxicity is one of the major problems affecting crop production. Boron (B) is an essential micronutrient for higher plants. In the present study, we investigated the alleviation of Al-induced inhibition of root growth and physiological characteristics by B in rapeseed. The rapeseeds were grown in different Al concentrations (0 and 300 μM), and for every concentration, two B treatments (2.5 and 25 µM as H3 BO3 ) were applied. The results showed that Al toxicity under low B drastically inhibited root growth. The supply of B improved root length, photosynthesis, root activity, total chlorophyll by 60.15%, 104.7%, 102%, and 106.3%, respectively under Al toxicity. This further resulted in improvement of peroxidase, catalase, and ascorbate peroxidase activities while decreasing malondialdehyde, H2 O2, and Al contents in roots and leaves. It might be supposed that B alleviates Al toxicity by less mobilization of Al in plant parts and through improving antioxidant enzyme activities.